Visual acuity outcome of stable proliferative diabetic retinopathy following initial complete panretinal photocoagulation. Issue 1 (29th September 2022) - Fu, Dun Jack; Thottarath, Sridevi; Faes, Livia; Balaskas, Konstantinos; Keane, Pearse A; Sim, Dawn; Sivaprasad, Sobha
Abstract : Background: Recent clinical trials on proliferative diabetic retinopathy (PDR) show that presenting visual acuity can be stabilised with panretinal photocoagulation (PRP) within 2 years despite the need for supplementary PRP or anti-vascular endothelial growth factor therapy for concomitant diabetic macular oedema (DMO). It is unclear whether similar results can be obtained in daily clinical practice. Here, we query the probability of vision loss in patients with treatment-naïve PDR who have attained stability after PRP and its predictors. Methods: Retrospective cohort study at a tertiary eye centre between 01 January 2015 and 31 December 2019, wherein 2336 eyes met study criteria with first record of stable PRP-treated PDR in at least one eye. Kaplan-Meier and Cox proportional hazards modelling were used to report the probability of vision loss of at least five Early Treatment Diabetic Retinopathy Study (ETDRS) letters. Results: The probability of losing at least five ETDRS letters was 50% at 3.32 (95% CI, 2.94 to 3.78) years after achieving first stability post PRP in treatment-naïve PDR. The mean decrease at this event was 14.2 (SD 13.0) ETDRS letters irrespective of the presence of DMO. The strongest risk factor for vision loss was a history of DMO at baseline (HR 1.62 (95% CI, 1.34 to 1.95), p<0.001). Discussion: One in two patients with stable treated PDR lose a line of vision by 3.5 years. This resulted in 15% of patients losing their eligibility to drive. Notably, 13% of the cohort died during the follow-up period.